Concise, efficient and highly selective asymmetric synthesis of (+)-(3S,4R)-cisapride - Davies, S; Huckvale, R; Lorkin, T; Roberts, P; Thomson, J (2011)
A concise asymmetric synthesis of the gastroprokinetic agent (+)-(3S,4R)-cisapride {(+)-(3S,4R)-N(1)-[3′-(4″-fluorophenoxy) propyl]-3-methoxy-4-(2″′-methoxy-4″′-amino- 5″′-chlorobenzamido)piperidine} from commercially available starting materials has been developed. The key step of this synthesis employs the diastereoselective conjugate addition of lithium (R)-N-benzyl-N-(α- methylbenzyl)amide to tert-butyl 5-[N-3′-(4″-fluorophenoxy)propyl-N- allylamino]pent-2-enoate and in situ enolate oxidation with (-)- camphorsulfonyloxaziridine to set the (3S,4R)-configuration found within the piperidine ring of the product. This synthesis proceeds in 9 steps from commercially available 1-(4′-fluorophenoxy)-3-bromopropane with an overall yield of 19%. © 2011 Elsevier Ltd. All rights reserved.